2023
DOI: 10.1002/fsn3.3414
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of microencapsulated probiotics modulates gut health and intestinal microbiota

Abstract: The beneficial effect of probiotics on host health is impaired due to the substantial loss of survivability during gastric transit caused by small intestinal enzymes and bile acids. Encapsulation helps to preserve the probiotics species from severe environmental factors. Lactobacillus paracasei, highly sensitive probiotic species to gastric acid, was encapsulated with polyacrylate resin. C57BL/6 male mice were equally divided into three groups; control group was fed with basal diet without any additives, the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…Some studies have shown that probiotics can improve intestinal flora disorders, affecting human metabolism, and immune functions (Akram et al., 2023 ; Gyawali et al., 2023 ). Our findings suggest that patients with hypothyroidism in early pregnancy combined with SIBO treated with probiotics had a higher rate of SIBO conversion and improvement of clinical symptoms such as abdominal distension.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that probiotics can improve intestinal flora disorders, affecting human metabolism, and immune functions (Akram et al., 2023 ; Gyawali et al., 2023 ). Our findings suggest that patients with hypothyroidism in early pregnancy combined with SIBO treated with probiotics had a higher rate of SIBO conversion and improvement of clinical symptoms such as abdominal distension.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, probiotics in fermented MFH also influence the composition of the gut microbiota. By supplementing mice with microencapsulated Lactobacillus paracasei , the researchers observed an increase in the proportion of lactic acid bacteria within the intestinal microbiota of the mice and an improvement in the intestinal barrier (Gyawali et al., 2023). Probiotics can maintain the homeostasis of the gut microbiota by exogenously supplementing or increasing the number of beneficial bacteria in the gut and competing with pathogens.…”
Section: Effects Of Probiotic‐fermented Mfh On Human Healthmentioning
confidence: 99%
“…It is recommended to practice good personal hygiene using mild detergents and avoiding strong antibacterial products to maintain intestinal microbiota balance. Consumption of probiotic- and prebiotic-rich beverages, containing live beneficial bacteria and food ingredients that support probiotic growth, respectively, is encouraged [ 115 , 116 , 117 ]. Furthermore, moderating smoking and alcohol consumption, ensuring adequate sleep, regular exercise, and stress management all contribute positively to preventing intestinal microbiota dysbiosis.…”
Section: Intervention and Treatment Strategiesmentioning
confidence: 99%